A distinct set of founders and fusion-competent myoblasts make visceral muscles in the Drosophila embryo. - San Martin, B.; Ruiz-Gomez, M.; Landgraf, M.; Bate, M. (Development, 2001)
The embryonic Drosophila midgut is enclosed by a latticework of longitudinal and circular visceral muscles. We find that these muscles are syncytial. Like the somatic muscles they are generated by the prior segregation of two populations of cells: fusion-competent myoblasts and founder myoblasts specialised to seed the formation of particular muscles. Visceral muscle founders are of two classes: those that seed circular muscles and those that seed longitudinal muscles. These specialisations are revealed in mutant embryos where myoblast fusion fails. In the absence of fusion, founders make mononucleate circular or longitudinal fibres, while their fusion-competent neighbours remain undifferentiated.